Techno-Assessment of the Use of Recycled Plastic Waste in Rammed Earth - Biswas, Wahidul; Zhang, Xihong (Mary Ann Liebert, 2021)
Effectively consumed plastic waste is an emerging technical and social issue for Australia. Adding plastic waste into construction material and ensuring minimised impact to the mechanical performance of the construction material could bring significant benefits. In this study, plastic waste material was mixed into cement-stabilised rammed earth (RE) material for brick manufacture. Techno framework consisting of compressive strength test and split tensile strength derivation for structural performance assessment and life cycle assessment for determining EE(EE) performance was applied to compare recycled high-density polyethylene (HDPE) added RE with conventional bricks. The compressive properties of different mixtures were studied. The replacement of conventional rock aggregates in stabilised RE brick with recycled plastic waste was found to improve the structural mechanical performance with the developed composition. Following this, an EE analysis was important to assess whether these waste-based bricks can improve environmental performance in a cost-competitive manner while maintaining structural performance. The increase of recycled HDPE in RE was found to likely affect the EE performance of RE, which could possibly be overcome by using less energy-intensive cementitious materials and recycled HDPE.